Useful Learning From Bachelor's Thesis to Professional Nursing Practice: A Qualitative Interview Study - Ani Henttonen RN, PhD; Marianne Teräs RN, PHN, M Health Sc, PhD; Max Scheja PhD; Bjöörn Fossum RN, PhD; Margareta Westerbotn RN, RM, MSN Ed (SAGE Open Nursing)
Introduction It is well-established in research that clinical learning during nursing education is a foundational preparation for future practice. However, the role of academic tasks, such as writing a bachelor's thesis, is less recognized for its contributions to nurses’ working lives and overall professional development. Objective This study aimed to explore registered nurses’ perceptions of the process of bachelor's thesis and its perceived usefulness in professional nursing careers. Methods Semistructured interviews with ten registered nurses was employed. A thematic analysis of the data and the framework of sustainable learning were used. Results The findings showed that the process of writing a bachelor's thesis during nursing education was perceived as a valuable learning experience and a source of continuing development. The main themes, professional knowing and professional agency, demonstrate the knowing applied in the healthcare contexts and for understanding nurse-patient relationships. The nurses stated that professional agency in research dissemination and a critical approach in their daily patient care was important and that the bachelor's thesis had provided a foundation for these practices. Conclusion Writing a bachelor's thesis during nursing education is justified as it may contribute to a critical understanding of nursing phenomena and the care taking place in clinical contexts. Bachelor's theses align with sustainable learning and are one of the prerequisites for readiness for change and development in professional practice.